People, power, Pollokshields. (15th August 2021) - Jarvis, Zoe J.; Anderson, Rory
Abstract : A social work perspective of dawn raids of refugees and asylum seekers within the Pollokshields area of Glasgow, which were stopped by community action. The hostile environment whipped up by politicians and the ongoing oppression of refugees and asylum seekers is considered within the context of counter terrorism legislation and the need for grassroots community social work working.